DEGUM, ÖGUM, SGUM and FMF Germany Recommendations for the Implementation of First-Trimester Screening, Detailed Ultrasound, Cell-Free DNA Screening and Diagnostic Procedures - Kozlowski, Peter; Burkhardt, Tilo; Gembruch, Ulrich; Gonser, Markus; Kähler, Christiane; Kagan, Karl-Oliver; von Kaisenberg, Constantin; Klaritsch, Philipp; Merz, Eberhard; Steiner, Horst; Tercanli, Sevgi; Vetter, Klaus; Schramm, Thomas (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
First-trimester screening between 11 + 0 and 13 + 6 weeks with qualified prenatal counseling, detailed ultrasound, biochemical markers and maternal factors has become the basis for decisions about further examinations. It detects numerous structural and genetic anomalies. The inclusion of uterine artery Doppler and PlGF screens for preeclampsia and fetal growth restriction. Low-dose aspirin significantly reduces the prevalence of severe preterm eclampsia. Cut-off values define groups of high, intermediate and low probability. Prenatal counseling uses detection and false-positive rates to work out the individual need profile and the corresponding decision: no further diagnosis/screening – cell-free DNA screening – diagnostic procedure and genetic analysis. In pre-test counseling it must be recognized that the prevalence of trisomy 21, 18 or 13 is low in younger women, as in submicroscopic anomalies in every maternal age. Even with high specificities, the positive predictive values of screening tests for rare anomalies are low. In the general population trisomies and sex chromosome aneuploidies account for approximately 70 % of anomalies recognizable by conventional genetic analysis. Screen positive results of cfDNA tests have to be proven by diagnostic procedure and genetic diagnosis. In cases of inconclusive results a higher rate of genetic anomalies is detected. Procedure-related fetal loss rates after chorionic biopsy and amniocentesis performed by experts are lower than 1 to 2 in 1000. Counseling should include the possible detection of submicroscopic anomalies by comparative genomic hybridization (array-CGH). At present, existing studies about screening for microdeletions and duplications do not provide reliable data to calculate sensitivities, false-positive rates and positive predictive values.Das Ersttrimester-Screening zwischen 11 + 0 und 13 + 6 Wochen mit qualifizierter Beratung, differenzierter Organdiagnostik sowie maternalen und biochemischen Markern ist die Grundlage der Entscheidung über den Umfang weiterer Untersuchungen. Mehr als die Hälfte relevanter fetaler Fehlbildungen können frühzeitig erkannt werden. Erhöhte Nackentransparenz und/oder auffällige biochemische Parameter weisen auf genetische oder strukturelle Anomalien hin. Durch Einschluss uteriner Dopplerparameter und des PlGF können die Risiken von Präeklampsie und Wachstumsrestriktion bestimmt und mittels der Gabe von ASS der weitere Verlauf zahlreicher Schwangerschaften positiv beeinflusst werden. Schwellenwerte (Cut-offs) und die Bildung von Bereichen hoher, intermediärer oder geringer Wahrscheinlichkeiten für das Vorliegen genetischer Anomalien dienen der Erläuterung der Erkennungs- und der Falsch-positiv-Raten. In der Beratung muss das individuelle Bedürfnisprofil der Schwangeren für entsprechendes Vorgehen (keine weitere Abklärung – Screening an zellfreier DNA – diagnostische Punktion) ermittelt werden. Die Beratung beinhaltet, dass in Kollektiven jüngerer Schwangerer und altersbedingt geringer Prävalenz oder beim Screening auf seltene submikroskopische Strukturanomalien auch bei hoher Spezifität der positive prädiktive Wert des Screenings gering ist. Innerhalb der Gesamtpopulation machen Trisomien und Anomalien der Geschlechtschromosomen etwa 70 % der lichtmikroskopisch erkennbaren Anomalien aus. Nach einem positiven Screening-Befund ist eine Absicherung durch diagnostische Punktion unerlässlich. Bei Testversagen besteht eine höhere Rate pathologischer Befunde. Die Verlustraten nach diagnostischen Punktionen liegen in Expertenhand um 1 bis 2 auf 1000 über der natürlichen Verlustrate. Die Beratung sollte die Möglichkeiten der Erkennung submikroskopischer Strukturanomalien mittels vergleichender genomischer Hybridisierung (Array-CGH) beinhalten. Belastbare Daten zu Sensitivität, Falsch-positiv-Raten und positiven prädiktiven Werten beim Screening auf Mikrodeletionen und -duplikationen lassen sich aus den bislang vorliegenden Studien nicht berechnen.
Keywords: cell-free dna; detailed early ultrasound; diagnostic procedures; chromosomal anomalies; first-trimester screening